Pernicious anaemia and Campylobacter like organisms; is the gastric antrum resistant to colonisation?. Issue 1 (January 1989) - Flejou, J F; Bahame, P; Smith, A C; Stockbrugger, R W; Rode, J; Price, A B
Abstract : Gastric biopsies from 86 patients with pernicious anaemia were examined for Campylobacter like organisms with particular attention to those showing an antral gastritis in addition to the usual pattern of body gastritis. All the patients had chronic atrophic gastritis in the body but Campylobacter like organisms were found at this site in only three patients. Thus the Type A pattern of gastritis (autoimmune) seen in patients with pernicious anaemia is only rarely associated with Campylobacter like organisms. Forty four of these patients had biopsies from body and antrum, 16 showed an antral gastritis of whom only one had Campylobacter like organism present. Twenty five of this latter group of patients were rebiopsied after five years. There was no change in the pattern of gastritis, and the same single patient remained colonised. The frequency of an antral gastritis in patients with pernicious anaemia was 36% yet the frequency of antral colonisation by Campylobacter like organisms was very low (6%). These results show that, as in the body, Campylobacter like organisms are not associated with gastritis when it occurs at this site in pernicious anaemia. The antral gastritis that may accompany body gastritis in pernicious anaemia seems more likely therefore to be an extension of primary type A body gastritis (autoimmune) rather than a secondary type B (chronic) gastritis and, it is argued, the antrum may exhibit resistance to colonisation.